Corporate environmental communication: a closer look at the initiatives from leading manufacturing and IT organizations in India. Issue 6 (21st February 2020) - Ramya, S.M.; Shereen, Aysha; Baral, Rupashree
Abstract : Purpose: This paper aims to investigate the level of environmental communication and the predominant themes of environmental initiatives and technologies used in India. Design/methodology/approach: In this exploratory study, a manual content analysis was conducted using print and website data related to corporate environmental communication of 60 Indian companies listed in the Bombay Stock Exchange, representing the top thirty from manufacturing and information technology (IT) sector each. Findings: The authors classified the level of importance based on seven attributes, distinguished between hard and soft disclosure and identified the prevalent environmental practices and technologies in each sector. The authors found that the environmental communication of the IT sector is technology-based than the manufacturing sector, but both are weak in acknowledging climate change. Practical implications: Managers, across the two sectors, can make their organizations environmentally responsible by learning and applying the current practices/technologies and reap benefits by mimetic isomorphism or create competitive advantage. Originality/value: Building on the theoretical and practical works in corporate sustainability and corporate social responsibility communication literature, the authors contribute to the stakeholder theory and voluntary disclosure theory. The findings of the study provide the much-needed base for future research that links the engineering and management community to take the scholarship further to prevent the climate crisis.